Pengembangan Instrumen Variabel Kemampuan Problem Solving pada Media E-Book - Mery Berlian; Radeswandri; Sohiron; Gitania Zulfianti (Milenial: Journal for Teachers and Learning, 2023)
Problem solving ability is an ability that must be possessed by students in solving various problems and being able to apply it in everyday life. The purpose of this study was to determine how far the effectiveness of problem solving variables for students in the learning process. This study uses the Research and Development (R&D) development model with an instrument in the form of a questionnaire consisting of 2 constructs. The survey study was carried out by involving 10 teachers from various schools. Data collection techniques were carried out by filling out online questionnaires, which were then analyzed with the help of the SPSS program. The results of the study prove that: 1) the preparation and development of the evaluation of the problem variable instrument on E-Book media for students in this study was carried out by testing 2 research constructs, namely 1) variable accuracy, and 2) variable effectiveness. As well as the results of testing the validity and reliability indicate that the data validity of the evaluation instrument meets the valid criteria. From this research, it shows that the developed instrument meets the requirements for use in the development of E-Book media.